PENERAPAN IPTEK SEKOLAH ADIWIYATA SMP NEGERI 4 PONTIANAK GUNA MEWUJUDKAN MASYARAKAT BERKARAKTER PEDULI LINGKUNGAN DI TEPIAN SUNGAI KAPUAS - Rahmahwati, Ratih; Kadaria, Ulli; Nurdini, Asriah (Universitas Mataram, 2025)
The partner in this PKM program is SMPN 4 Pontianak. Based on observations and interviews with partners, SMPN 4 Pontianak has been designated as an Adiwiyata school at the Pontianak city level. Currently, SMP Negeri 4 Pontianak aims to become a provincial-level Adiwiyata school. However, several problems have been faced, one of which is the low level of innovation in Adiwiyata activities. So this PKM activity aims to solve partner problems through the transfer of knowledge and technology related to processing waste into finished products that have added value from an economic perspective. In this PKM activity, several Adiwiyata training were carried out, namely training and assistance in using organic waste chopping machines and composters, eco-printing training, eco-bricks training, and Adiwiyata management training. It is hoped that this PKM Adiwiyata activity can help accelerate SMP Negeri 4 Pontianak to become a sustainable Adiwiyata school.